Hubungan Saturasi Oksigen dengan Mortalitas Penderita COVID-19 - Wiryawan, I Nyoman Bagus Putra; Sawitri, Endang; Rahmah Retnaningrum, Yuliana (Jurnal Medika : Karya Ilmiah Kesehatan, 2023)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) virus. There are several factors affecting mortality on patients COVID-19 such as oxygen saturation. This study aims to find the association of oxygen saturation with mortality among COVID-19 patients. The analytical observational research applied retrospective cohort study. There were 104 medical records of adult patients with the COVID-19 admitted to Abdoel Wahab Sjahranie Samarinda Regional Public Hospital from 2021 to 2022. The data were analyzed using Mann-Whitney test. There were 47 patients were confirmed deaths from COVID-19. The COVID-19 patients had a median oxygen saturation of 86%. The association between oxygen saturation and mortality was p = 0.001; OR = 1.163. In conclusion, there is an association between oxygen saturation and mortality among the COVID-19 patients